2017
DOI: 10.1039/c6ce02149b
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical growth of water-redispersible spheroidal gold nanoparticles assisted by leonardite humate

Abstract: The growth of gold nanoparticles (AuNPs) assisted by humatea natural hyperbranched polyelectrolytewas studied using in situ and ex situ techniques. The conditions for formation of almost monodisperse gold nanospheres of 13 ± 3 nm diameter with pronounced plasmonic properties were defined. A striking similarity was found between humate-and citrate-mediated growth of AuNPs: the formation of gold nanospheres involved rapid nucleation of gold seeds, slow growth within the intermediate agglomerates (visible as nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…reacting with H + or OH − ions from dissolved acids and bases (depending on pH value) and producing the positive (Fe-OH + 2 ) or negative (Fe-O − ) charges, respectively [9]. The changes of the surface charge affect the electrostatic repulsion between the nanoparticles and thus, the overall stability of the colloid according to the DLVO theory [9,18,19]. Here, we employed ζ-potential measurements to characterize the surface charge of γ-Fe 2 O 3 nanoparticles and their conglomerates with HA at pH range of 3 -10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…reacting with H + or OH − ions from dissolved acids and bases (depending on pH value) and producing the positive (Fe-OH + 2 ) or negative (Fe-O − ) charges, respectively [9]. The changes of the surface charge affect the electrostatic repulsion between the nanoparticles and thus, the overall stability of the colloid according to the DLVO theory [9,18,19]. Here, we employed ζ-potential measurements to characterize the surface charge of γ-Fe 2 O 3 nanoparticles and their conglomerates with HA at pH range of 3 -10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available potassium humate from leonardite (a highly oxidized variety of lignites) (Powhumus ® , Humintech GmbH, Grevenbroich, Germany) was used. Its basic properties, such as elemental and functional group analyses, 13 C NMR spectroscopy, and size exclusion chromatography have been reported earlier elsewhere [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, one can find reports on using HSs as a stabilizer for nanoparticles of metals [26,27] and oxides [28][29][30][31][32]. However, their use is not only limited to preventing aggregation of nanoparticles but it is suggested that derivatives of humic acid could play a role of a functional component, for example, in processes of water cleaning from heavy metals [33,34] and organic contaminants [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of silver NPs formation the reaction was carried out for 6 h and the color of reaction mixture was changed from colorless to dark brown. The principial reactions of the metal ions reduction by the citrate anions may be written as follows [50][51][52]:…”
Section: Reduction With Sodium Citratementioning
confidence: 99%
“…The presence of suspended titania particles may initiate the aggregation process of the initially stable metal NPs aqueous colloid suspension. Generally, to prevent the NPs aggregation, it may be reasonable to use well-stabilized water redispersible metal NPs, stabilized by humate polyanions [50], but the use of stabilizing agents affects on the metal/semiconductor contact due to the organic interlayer, and hence obtained materials are not applicable in photocatalysis. To quantify the particles size and compare the anisotropy of NPs, a statistical analysis was performed.…”
Section: Size and Morphologymentioning
confidence: 99%